Advanced Marjolin′s ulcer of the scalp in a 13-year-old boy treated by excision and free tissue transfer: Case report and review of literature - Daya M; Balakrishan T (Indian Journal of Plastic Surgery)
Marjolin′s ulcer originates in chronic scars and wounds of diverse origin. This relatively rare tumour is most commonly a squamous cell carcinoma. The reason for malignant transformation is not well understood. The burn scar is a common predilection. We present the youngest patient in the literature, a 13-year-old male with a locally advanced squamous cell carcinoma of the scalp with intracranial extension following an unhealed burn injury at the age of three. Bilateral cervical lymphadenopathy was also noted. The tumour was excised and the large defect overlying the brain was covered by free latissimus dorsi musculocutaneous flap. At four weeks a therapeutic bilateral selective neck dissection was done. Adjuvant chemotherapy was administered. This report reiterates the importance of early diagnosis. Free tissue transfer further enhances our ability to cover complex defects associated with excision of advanced lesions.